2013
DOI: 10.1099/vir.0.049940-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence among members of the Kokobera group of flaviviruses supports their separation into distinct species

Abstract: The Kokobera virus group comprises mosquito-borne flaviviruses that cluster together phylogenetically. These viruses are unique to Australia and Papua New Guinea, and have been associated with a mild polyarticular disease in humans. Recent isolation of genetically diverse viruses within this group has prompted analysis of their genetic and phenotypic relationships. Phylogenetic analysis based on complete ORF, the envelope gene or the NS5/3′ untranslated region supported the separation of the group into distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 27 publications
(44 reference statements)
1
13
0
Order By: Relevance
“…Nucleotide alignments with the complete 10874 nt KOKV genome sequence indicated that the Bainyik virus was more closely related to it than STRV or the Torres virus, as expected (nucleotide identity scores: KOKV-Bainyik virus, 80.4%; KOKV-STRV, 73.5%; KOKV-Torres virus, 74.3%). This was consistent with previous reports based on analyses of the untranslated regions (UTR) and envelope sequences (1). The putative complete open reading frame (ORF) was obtained for all three viruses (STRV, 3,414 aa; Bainyik virus, 3,410 aa; and Torres virus, 3,412 aa) which was similar to KOKV which has an ORF size of 3,410 aa.…”
Section: Genome Announcementsupporting
confidence: 94%
See 3 more Smart Citations
“…Nucleotide alignments with the complete 10874 nt KOKV genome sequence indicated that the Bainyik virus was more closely related to it than STRV or the Torres virus, as expected (nucleotide identity scores: KOKV-Bainyik virus, 80.4%; KOKV-STRV, 73.5%; KOKV-Torres virus, 74.3%). This was consistent with previous reports based on analyses of the untranslated regions (UTR) and envelope sequences (1). The putative complete open reading frame (ORF) was obtained for all three viruses (STRV, 3,414 aa; Bainyik virus, 3,410 aa; and Torres virus, 3,412 aa) which was similar to KOKV which has an ORF size of 3,410 aa.…”
Section: Genome Announcementsupporting
confidence: 94%
“…The Kokobera group of flaviviruses (family, Flaviviridae ; genus, Flavivirus) currently includes 5 candidate species: Kokobera (KOKV), Stratford (STRV), Bainyik (previously strain MK7979), Torres (previously strain TS5273), and New Mapoon (NMV) viruses (1). The prototype strain for this group, KOKV, was first isolated in 1960 in Mitchell River Mission in northern Queensland, Australia, from Culex annulirostris mosquitoes (2), and more recently from Sabai Island and Cape York Peninsula, Australia (3, 4).…”
Section: Genome Announcementmentioning
confidence: 99%
See 2 more Smart Citations
“…In Australia, infection with WNV KUN has been observed in horses, but the disease has rarely been confirmed [5], while cases of equine MVEV-encephalitis are mostly, but not exclusively, seen under the same environmental conditions as those precipitating human MVEV cases (Barton et al , [6], unpublished data). Other flaviviruses circulating in Australia, but generally considered apathogenic or with very low virulence in mammals include Kokobera virus (KOKV), Stratford virus (STRV), Alfuy virus (ALFV) and Edge Hill virus (EHV) [7,8,9,10]. An incursion of JEV occurred in 1995 in the Torres Strait, but the virus did not become endemic and has not been diagnosed on the Australian mainland since 1998 [11,12,13].…”
Section: Introductionmentioning
confidence: 99%